Copper-catalyzed C–O bond cleavage and cyclization: synthesis of indazolo[3, 2-b]quinazolinones. Issue 10 (10th January 2017) - Qiao, Rui; Ye, Leping; Hu, Kun; Yu, Shuling; Yang, Weiguang; Liu, Miaochang; Chen, Jiuxi; Ding, Jinchang; Wu, Huayue
Abstract : Cu-catalyzed sequential inert C–O bond cleavage followed by intramolecular C–N bond formation for the synthesis of indazolo[3, 2- b ]quinazolinones. Abstract : The first example of a copper-catalyzed halogen-free protocol to construct indazolo[3, 2- b ]quinazolinones was developed through sequential inert C–O bond cleavage followed by intramolecular C–N bond formation. This protocol represents an efficient synthetic tool for accessing a more diverse range of functionalized indazolo[3, 2- b ]quinazolinones. The structure of the newly synthesized indazolo[3, 2- b ]quinazolinones was unambiguously confirmed by X-ray crystal diffraction analysis.